Relations between emotion and working memory: Evidence from behavioural and psychophysiological studies - Ribeiro, Fabiana Silva; Albuquerque, Pedro Barbas; dos Santos, Flávia Heloísa [UNESP] (My University, 2018)
Baddeley (2007) proposed the Hedonic Detection to explain the connection between emotion and working memory (WM). This review aimed to systematize evidence of the influence of emotion on performance of WM tasks and its association with the Hedonic system on current studies. We carried out a database research that generated 103 papers in a restricted period (2007-2017). Ten papers combining behavioural tests with psychophysiological measures and ten papers using strictly behavioural tasks were selected. In all approaches were observed that the type of cognitive request underlying the task is crucial to understand how WM performance is influenced by emotion. Besides, was possible to detect a trend in the literature to focus on executive process related to a neural model for WM, since just only one behavioural paper explained the results based on Hedonic Detector system.
Relações entre emoção e memória operacional: Eviděncias de estudos comportamentais e psicofisiológicos
Keywords: Emotion; Systematic review; Working memory